2013
DOI: 10.1590/1414-431x20132643
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the use of nanocapsules in oncology

Abstract: The application of nanotechnology to medicine can provide important benefits, especially in oncology, a fact that has resulted in the emergence of a new field called Nanooncology. Nanoparticles can be engineered to incorporate a wide variety of chemotherapeutic or diagnostic agents. A nanocapsule is a vesicular system that exhibits a typical core-shell structure in which active molecules are confined to a reservoir or within a cavity that is surrounded by a polymer membrane or coating. Delivery systems based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 88 publications
(138 reference statements)
0
12
0
Order By: Relevance
“…Vakilinezhad et al [22] described PLGA nanoparticles containing CUR and MTX with an initial burst release that was attributed to the drug dispersion into the superficial layers of these particles. In the present study, a typical core-shell structure was strategically planned to avoid this effect and to achieve a prolonged drug release for circumventing the administration of multiple doses per day of chemotherapy [42].…”
Section: In Vitro Drug Release Studymentioning
confidence: 99%
“…Vakilinezhad et al [22] described PLGA nanoparticles containing CUR and MTX with an initial burst release that was attributed to the drug dispersion into the superficial layers of these particles. In the present study, a typical core-shell structure was strategically planned to avoid this effect and to achieve a prolonged drug release for circumventing the administration of multiple doses per day of chemotherapy [42].…”
Section: In Vitro Drug Release Studymentioning
confidence: 99%
“…These features have made biodegradable polymeric nanocpasules (NCs) one of the most widely used. They can achieve high water insoluble drug loading, facilitate intratumoral distribution, and protect the active agent from premature degradation, allowing its sustained and controlled release . NCs exhibit a typical core–shell structure in which active molecules are confined to an oil‐core that is surrounded by a polymer membrane or coating .…”
Section: Introductionmentioning
confidence: 99%
“…intratumoral distribution, and protect the active agent from premature degradation, allowing its sustained and controlled release. [2][3][4] NCs exhibit a typical core-shell structure in which active molecules are confi ned to an oil-core that is surrounded by a polymer membrane or coating. [ 5 ] Curcumin, has shown a wide range of pharmacological activities and has attracted great interest due to the possibility of tumor growth inhibition via multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[15] However, cationic liposomes can be disadvantageous because of their potentially high cytotoxicity. [17,22] The use of neutral lipids has thus been investigated, and studies have demonstrated that they are more biocompatible and have superior pharmacokinetics when compared to their cationic counterparts. Entrapment efficiency of siRNA does decrease with neutral lipids, but modifications can be made to the neutral lipoplexes to increase entrapment efficiency.…”
Section: Lipoplexesmentioning
confidence: 99%
“…[25,30,31] Dendrimers are also similar to lipid-based vectors due to high cytotoxicity being associated with not only cationic lipid-based vectors but cationic dendrimers as well. [17,22,30] However, dendrimers can also be modified through PEGylation to not only increase the duration of its circulation in the blood but also to decrease its toxicity and increase its transfection efficacy. [32] The last/outer generation on the dendrimer (each concentric layer of a dendrimer is considered a generation) has a specific amount of functional groups that can be produced to ensure wanted interactions with appropriate tissues.…”
Section: Dendrimersmentioning
confidence: 99%